Usability of the internal mammary recipient vessels in microvascular breast reconstruction. Issue 7 (July 2016) - O'Neill, Anne C.; Hayward, Victoria; Zhong, Toni; Hofer, Stefan O.P.
Summary: Background and aim: Although the internal mammary vessels are, for many surgeons, the recipient vessels of choice in microvascular breast reconstruction, there continues to be some debate regarding their use. The reliability of these vessels, particularly the vein, has been called into question, with high rates of conversion to alternative vessels being reported. This study investigates the true usability rate of the internal mammary vessels in a large series of consecutive patients without preselection. Methods: A review of all patients who underwent microvascular breast reconstruction at the University Health Network between September 2007 and December 2013 was conducted, and the conversion rate to alternative vessels was determined. Results: A total of 759 microvascular breast reconstructions were performed in 515 patients. The internal mammary vessels were explored in all cases and found to be suitable for anastomosis in 756 of 759 reconstructions. Conversion to the thoracodorsal vessels was required in three reconstructions (0.4%) due to unusable internal mammary arteries. There was no significant increase in unusable vessels with timing or laterality of reconstruction or other factors such as smoking, vascular co-morbidities and adjuvant chemotherapy or radiotherapy. Total flap failure occurred in four reconstructions (0.5%), whereas partial flap loss occurred in five (0.6%). Conclusion: The internal mammary vessels can be safely and reliably used in almost all patients undergoing microsurgical breast reconstruction with low rates of microvascular complications.